2015
DOI: 10.5293/ijfms.2015.8.1.023
|View full text |Cite
|
Sign up to set email alerts
|

Rotordynamic Performance Measurements of An Oil-Free Turbocharger Supported on Gas Foil Bearings and Their Comparisons to Floating Ring Bearings

Abstract: This paper presents the rotordynamic performance measurement of oil-free turbocharger (TC) supported on gas foil bearings (GFBs) for 2 liter class diesel vehicles and comparison to floating ring bearings (FRBs). Oil-free TC was designed and developed via the rotordynamic analyses using dynamic force coefficients from GFB analyses. The rotordynamics and performance of the oil-free TC was measured up to 85 krpm while being driven by a diesel vehicle engine, and compared to a commercial oil-lubricated TC supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The analysis was carried out for both fully floating ring and semi-floating ring bearings. Lee et al 10 illustrated the effect of gas foil bearings on dynamics of turbocharger rotor and compared the results of the rotor with floating ring bearings. Peng et al 11 suggested a material selection approach for turbocharger floating ring bearings.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis was carried out for both fully floating ring and semi-floating ring bearings. Lee et al 10 illustrated the effect of gas foil bearings on dynamics of turbocharger rotor and compared the results of the rotor with floating ring bearings. Peng et al 11 suggested a material selection approach for turbocharger floating ring bearings.…”
Section: Introductionmentioning
confidence: 99%
“…The test results revealed a stable TC rotor operating at a maximum speed of 121,500 r/min with low vibration amplitude and good shock tolerance. Since 2011, Lee et al [10][11][12] did many efforts to verify oil-free TCs. Among these studies, the rotordynamic characteristics were first analyzed, and then the oil-free TC rotors with diameters of 23.2 and 24 mm were operated and tested.…”
Section: Introductionmentioning
confidence: 99%